2015
DOI: 10.1063/1.4907182
|View full text |Cite
|
Sign up to set email alerts
|

Local geometric and electronic structures and origin of magnetism in Co-doped BaTiO3 multiferroics

Abstract: We have prepared polycrystalline samples BaTi1−xCoxO3 (x = 0–0.1) by solid-state reaction. X-ray diffraction and Raman-scattering studies reveal the phase separation in crystal structure as changing Co-doping content (x). The samples with x = 0–0.01 are single phase in a tetragonal structure. At higher doping contents (x > 0.01), there is the formation and development of a secondary hexagonal phase. Magnetization measurements at room temperature indicate a coexistence of paramagnetic and weak-ferromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…The intensity and sharpness of the spectra have rather decreased in the sample of x = 0.100, which confirms that the phase transition is observed in the XRD results, also confirms that the different vibration bands in Raman spectra of the Mn-doped BCZT samples are in agreement with the changes in the phase contents of the corresponding XRD patterns [23]. Compared with pure BCZT ceramics, a significant shift exists at * 740 cm -1 in BCZTM (x = 0.010) with a sharp peak at * 700 cm -1 , which is probably a consequence of defects caused by Mn-doping [24].…”
Section: Resultssupporting
confidence: 82%
“…The intensity and sharpness of the spectra have rather decreased in the sample of x = 0.100, which confirms that the phase transition is observed in the XRD results, also confirms that the different vibration bands in Raman spectra of the Mn-doped BCZT samples are in agreement with the changes in the phase contents of the corresponding XRD patterns [23]. Compared with pure BCZT ceramics, a significant shift exists at * 740 cm -1 in BCZTM (x = 0.010) with a sharp peak at * 700 cm -1 , which is probably a consequence of defects caused by Mn-doping [24].…”
Section: Resultssupporting
confidence: 82%
“…They believed that the system of isolated paramagnetic centers of Co 4+ ions produced a paramagnetic state in the samples. It was in good agreement with the work reported by Liu et al 9 Meanwhile, Phan et al 10 observed the co-existence of paramagnetic and weak ferromagnetic behavior in BaTi 1− x Co x O 3 samples (0.0< x ≤0.1). Using X-ray absorption spectra data, they explained that the paramagnetic nature was due to isolated Co 2+ and Co 3+ centers, in which the Co 3+ ions played a dominant role in enhancing the paramagnetic behavior.…”
Section: Introductionsupporting
confidence: 92%
“…[14][15][16][17][18][19] Li et al 15 observed that the tetragonal structure of BaTi 1Àx Co x O 3 (0.01# x #0.20) samples only exist at x #0.03, and it is transformed gradually to a hexagonal structure when Co content increases up to the value of 0.05. Phan et al 10 observed that tetragonal-hexagonal transformation occurs at x ¼ 0.01 in BaTi 1Àx Co x O 3 (0.0< x #0.1). However, a few works paid attention investigating the optical, dielectric characteristics, and conductivity mechanism of Co-doped BTO.…”
Section: Introductionmentioning
confidence: 99%
“…The modes around 530 cm −1 are mainly derived from the vibrations of oxygen displacements, and the modes beyond 700 cm −1 are known to correlate with the presence of oxygen vacancies. In BCZTM and BCZTC, the peaks at ~ 700 cm −1 are sharp, which may originate from the defects induced by Mn and Co doping . Moreover the asymmetry and disorder of the crystal structure can be inferred from the broadening and offset of Raman spectra, which are caused by the phase transition…”
Section: Resultsmentioning
confidence: 99%
“…In BCZTM and BCZTC, the peaks at ~ 700 cm −1 are sharp, which may originate from the defects induced by Mn and Co doping. 31 Moreover the asymmetry and disorder of the crystal structure can be inferred from the broadening and offset of Raman spectra, which are caused by the phase transition. 32 The SEM images of the sintered BCZT ceramics, as shown in Figure 3, further demonstrate the surface morphologies.…”
Section: Resultsmentioning
confidence: 99%